2014
DOI: 10.1080/13607863.2013.875125
|View full text |Cite
|
Sign up to set email alerts
|

The role of reading on the health and well-being of people with neurological conditions: a systematic review

Abstract: The effect of 'lone' reading, reading aloud and shared reading groups on the health and well-being of people with neurological conditions is currently an under-researched area. Although this review reports encouraging results of positive effects, the results should be viewed with caution due to the lack of randomisation, the small numbers of participants involved, and the limited and heterogeneous evidence base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“… Latchem and Greenhalgh (2014) conducted a systematic review of the effects of reading on health and well-being of people with neurological conditions. They concluded that some positive effects are discernible, although they caution against excessive optimism due to the small number of high-quality studies.…”
Section: Resultsmentioning
confidence: 99%
“… Latchem and Greenhalgh (2014) conducted a systematic review of the effects of reading on health and well-being of people with neurological conditions. They concluded that some positive effects are discernible, although they caution against excessive optimism due to the small number of high-quality studies.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from studies support the positive effect of reading on health and well-being (Latchem & Greenhalgh, 2014 ). Lucas et al ( 2019 ) highlighted that bibliotherapy (a projective indirect intervention involving storytelling or the reading of specific texts to treat psychological disturbance) can be used in building social relationships, empathy, resilience, solving problem skills, self-confidence, and assertiveness.…”
Section: Strength-based Trainingmentioning
confidence: 99%
“…The therapeutic benefit of reading was first identified by the ancient Romans and Greeks and can be found in theories by well-known scholars and thinkers throughout history (17,18). In "Poetics, " the Greek philosopher Aristotle (384-322 BC) presented the concept of using literature and drama for healing and purification (catharsis) of negative emotions.…”
Section: Historymentioning
confidence: 99%
“…Despite a call for more evidence-based research about the wider effectiveness of bibliotherapy (11,18,30,39,48,49), the reported benefits and zero harm makes bibliotherapy an effective form of therapy for individuals with mental and personal development issues (30,49). Bibliotherapy can be useful for health professionals and physicians.…”
Section: Caregivers and Health Teamsmentioning
confidence: 99%